Intervención arquitectónica al edificio con carácter patrimonial hotel Maitamá, utilizando la estrategia de adición de usos para la revitalización del centro de la ciudad (2020)
Founded on October 14th 1889 and located in the central mountain range, Armenia is a city currently inhabited by 2.959.694 citizens. One of its characteristic values is its cultural heritage. This heritage drives an active tourism industry which is in direct conflict with the conservation of said heritage.The earthquake which occurred in 1999 gave way to the reconstruction of the city, this had negative consequences in terms of the identity of the region. This process triggered different actions such as: foreign investment, speed in policies for local budget execution in the reconstruction of infrastructure, the incorporation of new concepts in housing construction alien to the culture itself, disarticulation of projects with the context of heritage and architecture of the city, among others.Over time, the buildings that make up this city centre have deteriorated, disconnecting with the urban dynamics of the inhabitants. As the years went by, housing construction was moving further away from the city center, abandoning the old dynamics of meeting, historical tradition of coffee, and expression of activities.The research is focused on providing an articulated solution to this problem by designing a housing project within a heritage building. The Hotel Maitamá building had a great influence on the development of urban dynamics when built in 1946, but overtime and as a result of the earthquake catastrophe all this was forgotten, leaving behind a reminiscent historic urban identity and the essence of what the city was.Intertwining the past and modern thought, the proposal to recover the hotel has an emphasis on the concepts of contemporary urbanism, historical revitalization, rehabilitation, consolidation, recovery and the city as a museum.This mixed use offers the inhabitants what they need by adapting the spaces to suit the dynamics of the users; places of work, collective study and spaces of social interaction. The project provides working and academically active people, who require apartments in which all the services are offered; a space of rest adjusted to their needs together with what the centre of the city offers them: work, administrative centre, commercial centre and educational centre.